CXCR4 and PD-1 Expression in Head and Neck Cancer with Perineural Spread - Barnett, Catherine M.; Sommerville, Ryan S.; Lin, Charles; Ratnayake, Gishan; Hughes, Brett; Taheri, Touraj (Journal of Neurological Surgery Part B: Skull Base, 2019)
Background Perineural spread (PNS) is a marker of aggressiveness and has been shown to occur in cranial nerves due to advanced mucosal and cutaneous head and neck cancer. Receptors CXC chemokine receptor 4 (CXCR4) and programmed cell death-1 (PD-1) have been shown to be overexpressed in a variety of cancers with PNS, with the inhibition of these pathways offering a potential future treatment.Methods Retrospective immunohistochemical staining for the CXCR4 and PD-1 receptors was performed on 28 head and neck specimens that demonstrated PNS from January 2017 to August 2017, at Royal Brisbane and Women's Hospital, Brisbane, Australia.Results CXCR4 staining was positive in 52 and 60% of the squamous cell carcinoma (SCC) and adenoid cystic carcinoma PNS specimens, respectively. Cutaneous SCC tumors with no PNS stained positively in 33%. No significant staining for PD-1 in peritumoral lymphocytes or tumor specimens was seen.Conclusion CXCR4 is overexpressed in advanced skin cancer and head and neck tumors that demonstrated PNS to large cranial nerves. Overall, these results provide strong support for using CXCR4 as a biomarker and further investigation of immunotherapeutic agents that could inhibit tumor progression via targeting CXCR4 expression.
Keywords: CXCR4; PD-1; head and neck cancer; plerixafor; perineural spread; adenoid cystic carcinoma; squamous cell carcinoma